The territorial peace borders, state development, and international conflict - Gibler, Douglas M. (Cambridge University Press, 2012)
There is continued discussion in international relations surrounding the existence (or not) of the 'democratic peace' - the idea that democracies do not fight each other. This book argues that threats to homeland territories force centralization within the state, for three reasons. These forces explain why conflicts are associated with centralized states and in turn why peace is associated with democracy.